1995
DOI: 10.1161/01.atv.15.10.1774
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors for the In Vitro Assembly of Lp(a)

Abstract: Lp(a) is composed of an LDL-like core and the glycoprotein apo(a). Current evidence strongly suggests that the assembly of this atherogenic lipoprotein proceeds outside the liver cells in a two-step fashion. In the first step, a loose complex is formed involving kringle-4 motifs in apo(a) and one or more Lys side chains in apoB-100. In the second step, this complex is stabilized by a disulfide bridge. Indications are that Lp(a) assembly is critical in the determination of plasma apo(a) concentrations. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
49
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 45 publications
7
49
2
Order By: Relevance
“…Taken together, our data demonstrate that specific interactions between apo(a) KIV 7 and KIV 8 and Lys 680 and Lys 690 in apoB mediate a high affinity non-covalent interaction between apo(a) and low density lipoprotein, which dictates the efficiency of covalent Lp(a) formation.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Taken together, our data demonstrate that specific interactions between apo(a) KIV 7 and KIV 8 and Lys 680 and Lys 690 in apoB mediate a high affinity non-covalent interaction between apo(a) and low density lipoprotein, which dictates the efficiency of covalent Lp(a) formation.…”
supporting
confidence: 52%
“…Studies performed by several investigators have underscored the importance of KIV 6 (10,14,20,21) and possibly KIV 7 (10,14,21) in this process. Previous data from our group also suggest that the WLBS in apo(a) KIV 8 plays a major role in non-covalent binding to LDL (14); all studies to date have demonstrated no role for apo(a) KIV 5 . In the above studies, domains in apo(a) involved in non-covalent binding to apoB were identified by sequential truncation of full-length apo(a), followed by assessment of binding to immobilized LDL.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…17,18 Additionally, apoB94 lacks additional C-terminal sequences located between apoB95 and apoB97 that have been reported to be essential for efficient Lp(a) formation both in vitro and in vivo in transgenic mouse models. 19 These latter sequences may be potential sites for the interaction of apo(a) KIV 9 and apoB, which is necessary for disulfide bond formation, or may affect the presentation of Cys4326 for disulfide bond formation.…”
Section: Gabel Et Al November 1998mentioning
confidence: 99%
“…8 The generation of a number of recombinant expression systems for apo(a) has allowed for significant advances in our understanding of the process of Lp(a) formation. Studies examining Lp(a) assembly in vitro have led to the identification of inhibitors of the assembly process, including lysine, lysine analogues, and proline, 9,10 as well as a thorough examination of the contribution of specific kringle domains of apo(a) to the process of Lp(a) formation. It is now well accepted that Lp(a) formation is a 2-step process in which the initial noncovalent association of apo(a) with the apoB moiety of LDL is mediated by the weak lysine-binding sites present in kringle IV types 5-8 (KIV [5][6][7][8] ) of apo(a) 10 -12 and that this interaction likely precedes specific disulfide bond formation.…”
mentioning
confidence: 99%